2005
DOI: 10.1021/ja050945m
|View full text |Cite
|
Sign up to set email alerts
|

Electron Flow Generated by Gas Phase Exothermic Catalytic Reactions Using a Platinum−Gallium Nitride Nanodiode

Abstract: We report steady-state conversion of chemical reaction energy into hot electrons by ballistic injection into a platinum-gallium nitride (Pt/GaN) nanodiode during the platinum-catalyzed oxidation of carbon monoxide. Surface catalytic reactions of molecules from the gas phase generated continuous steady-state hot electron currents with energies at least that of Schottky barrier energy ( approximately 1 eV). These hot electron currents were observed on two different nanodiodes (Pt/TiO2 and Pt/GaN) and represent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 6 publications
2
57
0
2
Order By: Relevance
“…As the surface becomes less positively charged, the acetonitrile orientation flips 180° with the CH 3 group pointing toward the surface. We constructed a so called catalytic nanodiode (59)(60)(61), which is composed of a metal of thickness less than the mean free path of hot electrons, deposited on a semiconductor surface, as shown in Figure 8a. When exothermic catalytic chemical reactions occur, we find that the heat transferred is converted to a hot electron flow that can pass through the metal film into the semiconductor which has a Schottky barrier (62; 63), which allows the passing of energetic electrons in one direction but not in the other direction.…”
Section: Future Directions Of Molecular Surface Sciencementioning
confidence: 99%
“…As the surface becomes less positively charged, the acetonitrile orientation flips 180° with the CH 3 group pointing toward the surface. We constructed a so called catalytic nanodiode (59)(60)(61), which is composed of a metal of thickness less than the mean free path of hot electrons, deposited on a semiconductor surface, as shown in Figure 8a. When exothermic catalytic chemical reactions occur, we find that the heat transferred is converted to a hot electron flow that can pass through the metal film into the semiconductor which has a Schottky barrier (62; 63), which allows the passing of energetic electrons in one direction but not in the other direction.…”
Section: Future Directions Of Molecular Surface Sciencementioning
confidence: 99%
“…If the metal thickness is of the order of the electron mean free path, hot electrons can be collected during ballistic transport across the metal. Recent experimental 11-14 and theoretical 10,15 studies have demonstrated electronic excitations created during chemisorption and physisorption of gases at surfaces, and by chemical reactions at surfaces [16][17][18] .…”
mentioning
confidence: 99%
“…[8,33,101] [40,41,107] Wir detektierten einen Strom "heißer" Elektronen mithilfe einer Schottky-Diode. [38,39,106,108] Werden Metallpartikel [59] oder ein Film [109] mit Durchmessern bzw. einer Dicke ähnlich der mittleren freien Weglänge für Elektronen (ca.…”
Section: Ladungstransportunclassified